Sperm osteopontin mRNA expression levels and its correlation on semen quality and fertility in Madura bulls - Zulfi Nur Amrina Rosyada; Vincentia Trisna Yoelinda; Ekayanti Mulyawati Kaiin; Muhammad Gunawan; Mokhamad Fakhrul Ulum; Ligaya I.T.A Tumbelaka; Dedy Duryadi Solihin; Muhammad Agil; Asep Gunawan; Bambang Purwantara (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Rosyada ZNA, Yoelinda VT, Kaiin EM, Gunawan M, Ulum MF, Tumbelaka LITA, Solihin DD, Agil M, Gunawan A, Purwantara B. 2023. Sperm osteopontin mRNA expression levels and its correlation on semen quality and fertility in Madura bulls. Biodiversitas 24: 563-570. Osteopontin (OPN) gene transcripts influence spermatogenesis and germ cell development. Therefore, transcriptome analysis is needed to identify the fertility factor OPN in Madura bull sperm. Madura cattle are crosses originating from Bos indicus (zebu) and Bos javanicus (banteng). This study aims to examine sperm osteopontin (OPN) mRNA expression levels and its correlation with semen quality and fertility in Madura bulls. Frozen semen samples from Madura bulls were categorized as high-fertile (n: 4, average field conception rate: 78.28±3.25%) or sub-fertile (n: 4, average field conception rate: 66.73±5.01%). In post-thaw semen samples, sperm motility, viability, membrane, acrosome, and DNA fragmentation index were evaluated. OPN expression in sperm total RNA was analyzed using Real-Time Quantitative Polymerase Chain Reaction (RT-qPCR). The data analysis between the two fertility groups was assessed with Student's t-test and Pearson Square. Receiver-operating characteristic analysis and diagnostic sensitivity and specificity calculations were performed. Sperm motility, acrosome intact, and DFI differ (p<0.05) between groups, whereas viability and membrane plasma intact have no significance (p>0.05). In high-fertile Madura bulls, OPN mRNA was upregulated (p<0.05). The OPN mRNA expression had a strong correlation with the field conception rate (R: 0.807, P<0.05), sperm motility, and intact acrosome (R: 0.899, p<0.01; R: 0.804, p<0.05) respectively. In contrast, OPN negatively correlated with sperm DFI (R: -0.764, p<0.05). The OPN predicted bull fertility with 81.3% accuracy, 75% sensitivity, and 75% specificity. Thus, OPN may serve as a potential biomarker of Madura bull fertility.